Diurnal Dynamics of Gaseous and Dissolved Metabolites and Microbiota Composition in the Bovine Rumen - van Lingen, Henk J.; Edwards, Joan E.; Vaidya, Jueeli D.; van Gastelen, Sanne; Saccenti, Edoardo; van den Bogert, Bartholomeus; Bannink, André; Smidt, Hauke; Plugge, Caroline M.; Dijkstra, Jan (Frontiers in Microbiology, 2017)
Diurnal patterns of ruminal fermentation metabolites and microbial communities are not commonly assessed when investigating variation in ruminal CH4 production. The aims of this study were to monitor diurnal patterns of: (i) gaseous and dissolved metabolite concentrations in the bovine rumen, (ii) H2 and CH4 emitted, and (iii) the rumen microbiota. Furthermore, the effect of dietary inclusion of linseed oil on these patterns was assessed. Four multiparous rumen cannulated cows were used in a cross-over design with two 17-d periods and two dietary treatments: a control diet and a linseed oil supplemented diet (40% maize silage, 30% grass silage, 30% concentrate on dry matter (DM) basis for both diets; fat contents of 33 vs. 56 g/kg of DM). On day 11, rumen contents were sampled for 10 h after morning feeding to profile gaseous and dissolved metabolite concentrations and microbiota composition. H2 and CH4 emission was measured in respiration chambers from day 13 to 17. A 100-fold increase in ruminal H2 partial pressure was observed at 0.5 h after feeding, followed by a decline. Qualitatively similar patterns after feeding were also observed for H2 and CH4 emission, ethanol and lactate concentrations, and propionate molar proportion, although the opposite pattern was seen for acetate molar proportion. Increased H2 partial pressure may inhibit NADH oxidation, which shifts the fermentation to ethanol, lactate, and more propionate at the expense of acetate. Associated with this shift, a temporal biphasic change in the microbial composition was observed as based on 16S ribosomal RNA with certain taxa specifically associated with each phase. Bacterial concentrations were affected by time, and were increased by linseed oil supplementation. Archaeal concentrations tended to be affected by time and were not affected by diet, despite linseed oil supplementation tending to decrease the partial pressure and emission of CH4 and tending to increase propionate molar proportion. Linseed oil supplementation weakly affected microbiota composition, and was most associated with an uncultivated Bacteroidales taxon. In summary, our findings support the key role of the redox state of NAD in rumen fermentation and the importance of diurnal dynamics when understanding VFA, H2 and CH4 production.